INTERNAL BRANDING IN A SERVICE INDUSTRY- THE CASE OF BANKS IN GHANA - Yeboah, Johnson; Ewur, George Dominic; Adigbo, Evelyn Delali; Asirifi, Ernest K. (European Scientific Journal, ESJ, 2014)
In branding literature, the employee role is recognized as crucial in delivering the service as promised by the brand.The creation of a strong brand and the deliverance of perceived service quality are premised by employees’ ability to deliver on customer expectations.This paper, therefore, explores the differential effect that internally oriented initiatives have on an organization’s human capital and its subsequent impact on the organization’s brand.Acase-study approach is adopted using a qualitative methodology. Indepth interviews reveal that employees feel that their actions are vital to the brand, and findings from a survey of 500 respondents demonstrate positive relationships among internal branding and their brand promise delivery. The paper also helps to emphasize the importance of internal branding for customer attraction in the banking industry in Ghana.